Global prevalence of respiratory virus infections in adults and adolescents during the COVID-19 pandemic: A systematic review and meta-analysis - Schüz, Marit L.; Dallmeyer, Leonie; Fragkou, Paraskevi C.; Omony, Jimmy; Krumbein, Hanna; Hünerbein, Ben L.; Skevaki, Chrysanthi (International journal of infectious diseases, 2023)
•Rhinovirus/Enterovirus were predominant respiratory viruses during COVID-19 pandemic.•Virus prevalence was higher in non-COVID patients than in those who were COVID-coinfected.•For some viruses, prevalence increased in the second half when restrictions eased.•Non-SARS-CoV-2 prevalence decreased in many studies compared with pre-pandemic times.•No age-specific distribution of the viruses could be identified except for human metapneumovirus. Since the beginning of the COVID-19 pandemic, efforts have been made to contain the spread of the virus. However, the epidemiological burden of other respiratory viruses during the pandemic is unclear. We aim to address the epidemiology of respiratory viruses on adults/adolescents since the beginning of the pandemic. We systematically searched five databases and performed a meta-analysis to explore the pooled prevalence of respiratory viruses in different geographical regions, age groups, and periods and compared the prevalence between COVID-19 cases and non-COVID-19 patients. Enteroviruses/rhinoviruses were highly prevalent compared to other viruses. Different viruses were dominant in different regions. No significant differences in prevalence were found between different age groups, except for human metapneumovirus. There was an increase in prevalence of non-SARS-CoV-2 viruses in the second half of the pandemic (July 2021-December 2022). Comparison of COVID-19 and non-COVID patients showed a higher prevalence in the non-COVID group, significant for influenza, seasonal coronaviruses, and human parainfluenza viruses. Our findings indicate that enteroviruses/rhinoviruses were less impacted by healthcare measures compared with other respiratory viruses. The relaxation of measures in the second half led to an increased pooled prevalence of infections. Several factors may explain the lower prevalence among individuals infected with COVID-19.